Pain‐autonomic measures reveal nociceptive sensitization in complex regional pain syndrome. (10th October 2022) - Scheuren, Paulina S.; De Schoenmacker, Iara; Rosner, Jan; Brunner, Florian; Curt, Armin; Hubli, Michèle
Abstract: Background: Allodynia and hyperalgesia are common signs in individuals with complex regional pain syndrome (CRPS), mainly attributed to sensitization of the nociceptive system. Appropriate diagnostic tools for the objective assessment of such hypersensitivities are still lacking, which are essential for the development of mechanism‐based treatment strategies. Objectives: This study investigated the use of pain‐autonomic readouts to objectively detect sensitization processes in CRPS. Methods: Twenty individuals with chronic CRPS were recruited for the study alongside 16 age‐ and sex‐matched healthy controls (HC). All individuals underwent quantitative sensory testing and neurophysiological assessments. Sympathetic skin responses (SSRs) were recorded in response to 15 pinprick and 15 noxious heat stimuli of the affected (CRPS hand/foot) and a control area (contralateral shoulder/hand). Results: Individuals with CRPS showed increased mechanical pain sensitivity and increased SSR amplitudes compared with HC in response to pinprick and heat stimulation of the affected ( p  < 0.001), but not in the control area ( p  > 0.05). Habituation of pinprick‐induced SSRs was reduced in CRPS compared to HC in both the affected ( p  = 0.018) and slightly in the control area ( p  = 0.048). Habituation of heat‐induced SSR was reduced in CRPS in the affected ( p  = 0.008), but not the control area ( p  = 0.053). Conclusions: This is the first study demonstrating clinical evidence that pain‐related autonomic responses may represent objective tools to quantify sensitization processes along the nociceptive neuraxis in CRPS (e.g. widespread hyperexcitability). Pain‐autonomic readouts could help scrutinize mechanisms underlying the development and maintenance of chronic pain in CRPS and provide valuable metrics to detect mechanism‐based treatment responses in clinical trials. Significance: This study provides clinical evidence that autonomic measures to noxious stimuli can objectively detect sensitization processes along the nociceptive neuraxis in complex regional pain syndrome (CRPS) (e.g. widespread hyperexcitability). Pain‐autonomic readouts may represent valuable tools to explore pathophysiological mechanisms in a variety of pain patients and offer novel avenues to help guide mechanism‐based therapeutic strategies.